Exploring the use of the verbal intelligence quotient as a proxy for language ability in autism spectrum disorder. (May 2020) - Ribeiro de Oliveira, Leticia; Brian, Jessica; Kelley, Elizabeth; Beal, Deryk; Nicolson, Robert; Georgiades, Stelios; Iaboni, Alana; Fragiadakis, Susan Day; Ristic, Leanne; Anagnostou, Evdokia; Sanjeevan, Teenu
Highlights: Explored whether VIQ could be used as a proxy for language in ASD and typical development. VIQ scores were derived from a Wechsler scale and language scores were obtained from OWLS-II. VIQ accounted for a small proportion of variance in language scores across diagnosis and sex. VIQ is not a suitable measure of language content and use but may be used as a proxy for language content only. Abstract: Background: There is growing interest in understanding the brain and language associations in Autism Spectrum Disorder (ASD). A considerable number of studies investigating these associations have used the verbal intelligence quotient (VIQ) as their primary measure of language form and content. Given this current trend, we aimed to establish whether the VIQ could reliably be used as a measure of receptive and expressive language form and content in individuals with ASD and in typical development (TD). Method: We examined the VIQ standard scores derived from a Wechsler cognitive battery as well as receptive and expressive language standard scores from the Oral Written Language Scales – Second Edition (OWLS-II) of 714 participants aged 3–21 years: 488 with ASD and 226 with TD. Results: Regression analyses revealed that VIQ scores predicted greater variance in receptive and expressive language scores in males with ASD relative to males with TD, and predicted less variance in receptive and expressive language scores in females with ASD relative to females with TD. Overall, VIQ accounted for a small proportion of variance in receptive and expressive language scores. Conclusions: Our findings indicate that the VIQ does not accurately capture language form and content evaluated by language measures like the OWLS-II, but may perhaps be used as a proxy for language content only.